PENERAPAN METODE FORWARD CHAINING PADA SISTEM PAKAR REKOMENDASI JURUSAN - Rahmawati; Rusdiansyah (Jurnal Sistem Informasi, 2014)
Abstract— SMK is a choice of formal education junior high school students who will proceed to the top level who want to deepen the talent, skill and desire that is owned by a student. However, in general, most of the prospective students are confused to choose majors or even less informed about it that will take because so many options available majors. Often some vocational students who do not get along with their majors. It is therefore important to know more about their own interests in choosing majors, an understanding of each department, field of study that will be studied in the majors their would choose as well as job prospects would they do it later and majors in the College if they wish to pursue a higher level. Expert systems are knowledge-based program that provides solutions to problems with the quality of expert-problems within a specific domain. Expert System is a program of giving advice or consulting programs that contain knowledge and experience which is input by one or more experts in a particular domain, so that everyone can use to solve problems or make decisions assistence by an expert. In the field of education, expert systems can be utilized as a program giving advice or recommendation to designate a department in this case choosing majors in SMK HUTAMA that fit their talents and abilities they have. With the development of Internet technology as a medium for today's global information, allows Expert System is presented in the form of a web-based information system that can be accessed online anytime.